BIM-based life cycle assessment and life cycle costing of an office building in Western Europe. (February 2020) - Santos, Rúben; Costa, António Aguiar; Silvestre, José D.; Vandenbergh, Thomas; Pyl, Lincy
Abstract: The main aim of this research is to enhance the integration of life cycle assessment (LCA) and life cycle costing (LCC) methodologies with building information modelling (BIM), as existing approaches still have limitations (e.g. interoperability issues, non-editable databases). For that purpose, an automatic LCA/LCC analysis within a BIM-based environment is proposed. A BIM-based environmental and economic life cycle assessment (BIMEELCA) prototype tool was developed by the authors to improve the integration of BIM with LCA and LCC. Moreover, a pilot case study located in the Netherlands was used to validate the work developed in this research, thus demonstrating the usefulness of this approach for the construction industry. This study unveiled the potential of BIM-based simulations for the assessment of the environmental and economic impacts of buildings by integrating semantic information in the model. The work presented in this research is expected to contribute to the development of automatic sustainability simulations, creation of tailor-made BIM objects' libraries, and use of historical data contained within data-rich models for predictive analyses (i.e. analyses that identify the most suitable solutions based on the data from previous projects). Highlights: LCA and LCC analyses were performed on an office building in the Netherlands. Environmental, economic, and physical information were inserted in the BIM objects. An automatic Streamlined LCA/LCC analysis is possible in semantically-rich models. The BIM-LCA/LCC approach was compared with two other traditional approaches. This work is expected to contribute to the development of green BIM libraries.